Pre-harvest application of methyl jasmonate for improving nutritional quality of Pusa Navrang grape (Vitis vinifera) - SAHOO, TANUSHREE; VERMA, MAHENDRA KUMAR; DUBEY, ANIL KUMAR; THAKRE, MADHUBALA; IQUEBAL, MIRASIF; BHARADWAJ, C; SAHA, SUPRADIP (The Indian Journal of Agricultural Sciences, 2020)
The effect of pre-harvest application of Methyl Jasmonate (MeJA) on berry quality, flavonoid content and antioxidant capacity in grapes (Vitis vinifera L.) cv. Pusa Navrang were studied under subtropical conditions of New Delhi. Different doses of MeJA (0, 5, 10, 15 mM) were applied at three different dates. There were no significant differences were recorded for bunch and berry weight. Grapes treated with MeJA had slightly higher soluble solid content, lower titratable acids than untreated berries. Methyl jasmonate significantly enhanced the content of total monomeric anthocyanins, total phenolics, flavonoids and the antioxidant capacities in the berries. These were found significantly different for dose of methyl jasmonate and time of application. In general, when MeJA(10 mM) applied at veraison stage was found most effective for improving the berry bioactive compounds and had significantly higher total monomeric anthocyanin (1434.43 C3GE mg/kg fresh berry weight), total phenolic content (504.58 mg/100 g), total flavonoid content and antioxidant activity measured in terms of DPPH.